PENINGKATAN KREATIVITAS SISWA DALAM PEMBELAJARAN IPS KELAS IV MELALUI PROJECT BASED LEARNING DI SDN MERUYA SELATAN 01 JAKARTA BARAT KEC.KEMBANGAN - Mila Dwi Andini; Arita Marini; Chrisnaji Banindra Yudha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of students’ creativity in Social Studies learning in Grade IV of SDN Meruya Selatan 01 West Jakarta, as indicated by students’ limited ability to express ideas, provide varied answers, and actively participate in discussions. The objective of this study was to improve students’ creativity through the implementation of the Project Based Learning (PjBL) model. The research employed a Classroom Action Research method conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were 31 fourth-grade students of SDN Meruya Selatan 01 in the 2025/2026 academic year. Data were collected through observation, interviews, documentation, and creativity assessments. The results showed that the implementation of PjBL improved students’ creativity in Social Studies learning. Students became more active in discussions, generated more diverse ideas, and confidently presented their project outcomes. Improvements were observed in the aspects of fluency, flexibility, originality, and elaboration in completing project tasks. In addition, the learning atmosphere became more engaging and student-centered, which increased students’ participation in the learning process. Therefore, the Project Based Learning model is effective in improving students’ creativity in Social Studies learning in Grade IV of SDN Meruya Selatan 01 West Jakarta.